OPTIMALISASI SINKRONISASI DAN PENGEMBANGAN KURIKULUM SMK BHINA KARYA KARANGANYAR: UPAYA MENINGKATKAN KESESUAIAN LULUSAN DENGAN KEBUTUHAN INDUSTRI - Sudalyo, Ramadhian Agus Triono; Prasetyaningrum, Nurita Elfani (Jurnal Abdimas Bina Bangsa, 2024)
The Community Service (PkM) program titled Optimization of Curriculum Synchronization and Development at SMK Bhina Karya Karanganyar: Efforts to Align Graduates with Industry Needs aims to bridge the gap between the curriculum taught in vocational schools (SMK) and the demands of the industrial world, particularly in the era of the Fourth Industrial Revolution. This Workshop was held on July 3, 2024, involving all teachers from SMK Bhina Karya Karanganyar, as well as academics, practitioners, and industry representatives. The Workshop successfully deepened participants' understanding of the importance of curriculum synchronization through expert presentations that addressed industry-oriented curriculum development and the challenges faced by schools. Evaluation results showed that 85% of participants found this activity highly beneficial in enhancing their understanding of the curriculum development process relevant to industry needs. Group discussions identified several challenges, such as limited access to technology and industry involvement in curriculum development. However, strengthening the link and match program between schools and industries through internships, strategic partnerships, and teacher training was considered a potential solution. As a follow-up, the PkM team from Universitas Surakarta will assist in drafting relevant curriculum documents and training teachers, while also exploring partnerships with local industries to support student internship programs. With this curriculum synchronization, it is expected that SMK Bhina Karya Karanganyar graduates will be better prepared to meet the ever-evolving needs of the industry